Política de cotas no Instituto Federal de Educação, Ciência e Tecnologia do Tocantins - Campus Gurupi: reflexos da Lei nº 12.711, de 29 de agosto de 2012 - Castro, Fabíula Gomes de. (Universidade Federal do Tocantins, 2016)
It analyzed the vacancy reservation system based on racial and social criteria implemented at the Federal Institute campus Tocantins Gurupi. The dissertation aims to examine the experience of this educational institution from the perspective of students entering the reservation system of vacancies and managers in relation to the quota policy. Using the theoretical basis of legal, political and social fields, which focus on political and social meanings of affirmative action, it brings a discussion of these actions as public policies directed to ethnic, racial and social minorities approaching both the international and the Brazilian contexts. Following, it explores the affirmative action policy focused on education, specifically that which seeks to ensure access to higher and technical education to low-income people, black and brown through the quota system, based on Law n. 12.711/2012. The methodological procedures of research were the qualitative research and the case study. The instrument for data collection was the interview and the analysis was made through the methodology of Content Analysis. The empirical field was the IFTO Campus in Gurupi. The survey results indicate that the adoption of the Quota Law represented an undeniable improvement in the democratization of access to historically excluded groups. However, there is still a set of measures to be developed within the educational institutions to pursue its improvement.